AKUNTAN BERJIWA BELA NEGARA (STUDI EMPIRIS PADA MAHASISWA S1 AKUNTANSI UNIVERSITAS PEMBANGUNAN NASIONAL “VETERAN” JAWA TIMUR) - Dwi Suhartini; Hero Priono; Astrini Aning Widoretno; Galuh Tiaramurti (Behavioral Accounting Journal, 2019)
The purpose of this study is to analyze the factors that influence the learning process in the undergraduate programn Accounting department of "Veteran" UPN East Java in forming an accountant with the spirit of defending the country. Higher education has a very important role in developing the ability of individuals to be more insightful in science, technology, and the formation of good character. For this reason, effective learning models need to be developed in the campus environment, namely integrated learning models at the level of study programs by optimizing hard skills and soft skills in the learning process. The research method used is qualitative research with a phenomenological approach. The results of this study are there are still factors that can influence the learning process so that it becomes an obstacle in realizing learning outcomes to produce superior graduates with defending the country character. For this reason, in eliminating and reducing academic cheating, it requires learning methods of the Student Teams-Achievement Divisions (STAD) model to optimize hard skills and soft skills in forming a nation-wide accountant.